Factors Affecting the Achievement Level of Students of MBS: A Case Study of Shankar Dev Campus - Shah, Santosh Kumar; Yadav, Arun Kumar (Management Dynamics, 2018)
Shanker Dev Campus (SDC) one of the leading constituent Campus of TU is currently offering two years Master of Business Studies (MBS) programme in semester system. The article is to identify the significant factors affecting the achievement level of students of MBS I semester. The achievement level of the students is evaluated in terms of Semester Grade Point Average (SGPA) scores of the students. Required data were gathered from administration department of SDC. The SGPA scores of 500 passed students out of 1238 enrolled students were analyzed. The average SGPA score was significantly higher among the students whose father and mother engaged in non-agriculture occupation compared to others. The average SGPA score of students of Kathmandu valley was also significantly higher compared to other students. However, the differences in average SGPA scores by sex, caste/ethnicity, ecological region and development region were not found to be significant. Age, occupation of father and mother, location (Kathmandu valley and out of Kathmandu valley), class attendance of the students and marks obtained in bachelor were found significantly associated with SGPA scores of students where as sex and caste were found to be insignificant factors for SGPA score in simple regression model. The variables found to be significant factors of SGPA score from simple linear regression model were further analyzed through multiple regression model in which class attendance, marks obtained in bachelor and occupation of father were found to be significant factors of the achievement level of the students of MBS. The assumptions of multiple regressions including normality of residual, hetroscedasticity and multicollinearity were also tested for the valid inference.